Immunodiagnostic Methods: What Is Their Role in Areas of Low Endemicity? - Rafaella Fortini Queiroz Grenfell; Vanessa Silva-Moraes; Diana Taboada; Ana Carolina Alves de Mattos; Ana Karine Sarvel de Castro; Paulo Marcos Zech Coelho (The Scientific World Journal)
Worldwide Schistosomiasis mansoni continues to be a serious public health problem. Over the past decades, control programmes have made remarkable progress in reducing S. mansoni infections to a relatively low level in Brazil and African countries. Endemic regions are currently circumscribed in certain core areas where reinfection and repeated chemotherapy are frequent and, consequently, are related to residents with low parasite load. At present, diagnosis is predominately a key step for final disease control although low endemicity area residents are hardly detected by most of the available assays. In this paper, we review the current status and efforts made aiming at the improvement of diagnostic tools for S. mansoni in low endemicity infections. The establishment of diagnostic assays—simple, affordable, sensitive, and specific for field diagnosis of S. mansoni—is essential and should be given high priority.